Emergence of novel lineage of foot‐and‐mouth disease virus serotype Asia1 BD‐18 (G‐IX) in Bangladesh. Issue 2 (16th October 2019) - Ali, M. Rahmat; Alam, A. S. M. Rubayet Ul; Amin, Md. Al; Siddique, Mohammad Anwar; Sultana, Munawar; Hossain, M. Anwar
Abstract: Foot‐and‐mouth disease virus (FMDV) is a highly evolutionary divergent pathogen causing great economic havoc in many countries. Among its seven existing serotypes, Asia1 is the least divergent with a single topotype both genetically and antigenically. It is reported sporadically in Indian subcontinent and was classified under lineage G‐VIII. In 2018, serotype Asia1 re‐emerged in Bangladesh after 2013, along with circulation of a novel serotype Asia1 BD‐18 (G‐IX) lineage. VP1 phylogeny and sequence variation clearly demonstrated the novel strains which was estimated to have at least >5% nucleotide divergence with distinct clade formation. Also, the Bayesian phylogeographic inferences traced back to the origin time of lineage G‐IX in early 2017 and a possible origin in Bangladesh. Mutational analysis considering established eight lineages revealed that the virus strains belonged to lineage G‐IX contained a unique mutation at 44 position in the B‐C loop region of VP1. Inappropriate vaccination and inefficient outbreak surveillance possibly contributed to the current episode of emergence. Therefore, active surveillance and continued vigilance are essential to assess and timely detect the occurrence, extent and distribution of this novel Asia1 strains in Bangladesh and the neighbouring countries.